Penyusunan Bibliografi Beranotasi Subjek Hukum pada Buku Koleksi Perpustakaan Kepolisian Daerah Sumatera Barat - Hardianti, Rani; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe writing of this paper aims to: First, it is easy to compile a legal subject annotated bibliography to create a textbook at the West Sumatra Regional Police Library. Second, a definition that can be used in the preparation of an annotated legal subject bibliography at the Sumatra Bara Regional Police Library. Third, knowing the efforts made in the preparation of an annotated legal subject bibliography at the West Sumatra Regional Police Library.The method used is descriptive method that is giving anything or collecting data directly from the source. Data collected through direct observation at the West Sumatra Regional Police Library, grouping legal subject collections, typing book annotations, sewing author names and keyword indexes that were finally formulated and formats which are modern language formats (MLA) that can fit the quotation format more precisely for all research that is printed, for example is a book.Keyword: annotated bibliography, legal subject.